1999
DOI: 10.1007/s007750050289
|View full text |Cite
|
Sign up to set email alerts
|

Purification and spectroscopic studies on catechol oxidases from Lycopus europaeus and Populus nigra: Evidence for a dinuclear copper center of type 3 and spectroscopic similarities to tyrosinase and hemocyanin

Abstract: We purified two catechol oxidases from Lycopus europaeus and Populus nigra which only catalyze the oxidation of catechols to quinones without hydroxylating tyrosine. The molecular mass of the Lycopus enzyme was determined to 39,800 Da and the mass of the Populus enzyme was determined to 56,050 Da. Both catechol oxidases are inhibited by thiourea, N-phenylthiourea, dithiocarbamate, and cyanide, but show different pH behavior using catechol as substrate. Atomic absorption spectrosopic analysis found 1.5 copper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(75 citation statements)
references
References 0 publications
4
71
0
Order By: Relevance
“…In contrast, the catechol oxidase active site is, similar to tyrosinase and hemocyanin, a type 3 copper center [2,9,11,12,57]. That is, the copper centers are in nitrogen-rich coordination environments and are strongly antiferromagnetically coupled (and hence EPR-silent at X band).…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…In contrast, the catechol oxidase active site is, similar to tyrosinase and hemocyanin, a type 3 copper center [2,9,11,12,57]. That is, the copper centers are in nitrogen-rich coordination environments and are strongly antiferromagnetically coupled (and hence EPR-silent at X band).…”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…The activity was tested at different substrate concentrations. MichealisMenten-type substrate saturation behaviour, which is commonly observed at higher substrate concentrations in related model studies, [2,3,24] was not observed and the reaction rate was found to be independent of substrate concentration over the range studied (5-50 equiv). This phenomenon has been observed before, [7,11,25] and particularly strong binding of the substrate to the catalyst was proposed as a possible explanation.…”
Section: Wwwchemeurjorgmentioning
confidence: 60%
“…Copper proteins with a type-3 site, like hemocyanin and the enzymes tyrosinase and catechol oxidase are important dioxygenprocessing proteins [2][3][4][5][6]. These metallo-enzymes, which use molecular oxygen from air as the primary oxidant, are generally considered as very sophisticated catalysts.…”
Section: Discussionmentioning
confidence: 99%